Potential Mechanisms and Effects of Efferocytosis in Atherosclerosis - Wang, Lili; Li, Hongxia; Tang, Yuhan; Yao, Ping (Frontiers in Endocrinology, 2021)
Atherosclerosis (AS) is the main pathological basis for the development of cardio-cerebrovascular diseases. Abnormal accumulation of over-apoptotic and necrotic cells resulted in plaque enlargement, necrotic core formation and plaque rupture in AS. Under physiological conditions, apoptotic cells (ACs) could be effectively phagocytized and cleared by phagocyte-mediated efferocytosis. In contrast, the clearance efficiency of ACs in AS plaque was much lower because of the impaired efferocytosis in AS. Recent findings have made great progress on the molecular mechanisms of efferocytosis process and dynamic regulation, and its dysfunction on organismal health. Yet, there are still few effective treatments for this process. This article reviews the mechanism of efferocytosis and the role of efferocytosis in AS, highlighting a novel therapeutic strategy for AS, which mainly prevents the progression of plaque by targeting efferocytosis.